First year allied health student transition to a regional university. (10th December 2019) - Gray, Marion; Gordon, Susan; O'Neill, Maureen; Pearce, Wendy M.
Abstract: Objective: Students from regional and remote backgrounds are more likely to stay and work in regional and remote locations. Health students transition and retention at university impacts the retainment of a competent rural health workforce. This study aimed to examine the perceptions of allied health students as they reflected upon their first six weeks at university and identified strategies which enhanced these experiences. Design: A cross‐sectional study. Surveys were administered to students who then completed a reflection exercise. Data were analysed using Pearson correlation coefficient and chi‐squares. Setting: An Australian regional university. Participants: First year occupational therapy, physiotherapy and speech pathology students. Main outcome measures: Factors influencing the first 6 weeks at university. Results: One hundred and forty‐three students participated. Homesickness was the major challenge in transitioning to university life. Subthemes identified were adjusting to being away from home, adjusting to university culture and the mature‐aged student. Specific issues included a lack of familiarity with university campuses and services, being unprepared for the workload and confusion while learning new skills. Conclusion: Orientation week activities assist students transition into university and age‐appropriate and family‐friendly activities should be considered for mature‐age students. All students were found to benefit from support to address economic pressures and skill development focusing on coping with university workload. The development of regional university policy including these strategies is likely to enhance student success.